Balancing Inflammation and Central Nervous System Homeostasis: T Cell Receptor Signaling in Antiviral Brain TRM Formation and Function - Netherby-Winslow, Colleen S.; Ayers, Katelyn N.; Lukacher, Aron E. (Frontiers in Immunology, 2021)
Tissue-resident memory (TRM) CD8 T cells provide early frontline defense against regional pathogen reencounter. CD8 TRM are predominantly parked in nonlymphoid tissues and do not circulate. In addition to this anatomic difference, TRM are transcriptionally and phenotypically distinct from central-memory T cells (TCM) and effector-memory T cells (TEM). Moreover, TRM differ phenotypically, functionally, and transcriptionally across barrier tissues (e.g., gastrointestinal tract, respiratory tract, urogenital tract, and skin) and in non-barrier organs (e.g., brain, liver, kidney). In the brain, TRM are governed by a contextual milieu that balances TRM activation and preservation of essential post-mitotic neurons. Factors contributing to the development and maintenance of brain TRM, of which T cell receptor (TCR) signal strength and duration is a central determinant, vary depending on the infectious agent and modulation of TCR signaling by inhibitory markers that quell potentially pathogenic inflammation. This review will explore our current understanding of the context-dependent factors that drive the acquisition of brain (b)TRM phenotype and function, and discuss the contribution of TRM to promoting protective immune responses in situ while maintaining tissue homeostasis.